Group-based interventions to reduce gambling involvement among male football fans: a synopsis of findings from a feasibility study - Gerda Reith; Blair Biggar; Chris Bunn; Manuela Deidda; Craig Donnachie; Frankie Graham; Cindy Gray; Nicola Greenlaw; Kate Hunt; Matthew Philpott; Neil Platt; Robert D Rogers; et al. (Public Health Research, 2025)
Background Gambling is associated with serious social and health harms, including suicidal ideation and suicide attempts. The risk of these adverse effects increases with consumption and imposes a substantial economic burden to the National Health Service and wider society, beyond the negative impacts on individuals and their families. Sports betting is a major growth area for the gambling industry. Sports bettors are disproportionately male and younger, two risk factors for gambling harms. It is important to develop and implement preventative interventions that limit the escalation of gambling harms among this group. We report on the feasibility of an intervention delivered within and by professional football clubs, a setting which has proved highly successful in attracting men to other behaviour change interventions (e.g. weight loss). Methods In what was originally designed as a three-phase study, a face-to-face group-based intervention (Football Fans and Betting) was refined in Phase 1, for delivery by trained community coaches at professional football club stadia. Eight 90-minute weekly sessions included interactive ‘classroom-based’ education around gambling behaviours, the industry and impacts, and group-based physical activity to promote social connectivity. Phase 2 assessed the feasibility of approaches to recruitment and retention and the acceptability of Football Fans and Betting to both coaches and participants. Phase 3 was intended to comprise a pragmatic, two-arm pilot randomised controlled trial of the Football Fans and Betting intervention at four professional football clubs in England. Results Data collected from participants and coaches via one-to-one interviews, observations and focus groups revealed significant barriers to recruitment, despite considerable iterative efforts to optimise ‘branding’ and strategies. Many of our target population did not perceive themselves as needing support. Instead, Football Fans and Betting was attractive to those with more severe gambling symptomology but who were ineligible as they required more specialist safeguarding support than Football Fans and Betting offered. It proved problematic to promote Football Fans and Betting as a programme to prevent progression to more serious gambling harms to men who were embedded in social networks where gambling was perceived as normal. The irony that many professional football clubs partner with gambling companies was noted by participants and some expressed scepticism around club intentions for delivering Football Fans and Betting. Despite considerable efforts to run Football Fans and Betting at six English professional football clubs during 2022 and 2023, insufficient numbers were recruited and retained. Phase 3 did not take place as progression to a pilot trial was unviable. Despite low numbers participating in Football Fans and Betting, those who undertook the programme found it to be useful in supporting behaviour change and in providing greater insight into industry tactics. Football Fans and Betting was most successful in feasibility delivery when it was delivered within grassroots and local community contexts. Conclusions In the current climate of gambling industry penetration into professional football, promoting a gambling harms prevention intervention proved an insurmountable challenge. Limitations The study failed to attract sufficient numbers to the intervention. Future work Embedding Football Fans and Betting or similar interventions within footballing communities that are not hampered by commercial gambling arrangements should be considered, along with an emphasis on the importance of early intervention to prevent progression to serious harms from gambling. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme as award number NIHR127665. Plain language summary Why did we do this research? We wanted to explore ways to help people who might be at risk of harm from gambling. Gambling harm can cause serious problems for both individuals and society, affecting finances, relationships and health, and can include thinking about suicide or trying to harm oneself. We focused on sports betting because it is popular among younger men who are more likely to develop gambling issues. We aimed to create a programme to prevent these problems, working within professional football clubs, which have been successful in running programmes for men’s health, like weight loss. What did we do? We developed a programme called Football Fans and Betting and trained coaches at football clubs to run it. The programme included educational sessions about gambling harms, along with activities, such as five-a-side football, to promote social connections. We planned to test Football Fans and Betting in a pilot trial at four professional football clubs in England. What did we find? Despite significant efforts, we faced challenges getting people to join the programme. Some people did not think they needed help, while others with more severe gambling issues needed specialised support beyond what Football Fans and Betting offered. It was also hard to convince men in social circles where gambling was seen as normal to join. Some participants were sceptical about the intentions behind the football clubs’ delivery of Football Fans and Betting, when many of them also had partnerships with gambling companies. There was also stigma associated with gambling, which meant many men did not think they had a problem, or did not want to admit they did. Ultimately, we could not recruit enough participants to move forward with the planned trial. Despite this, the programme was more attractive to people with higher levels of gambling harm than we originally intended, and it identified a high level of unmet need among this group. The people who did take part in the study found it helpful, and thought there was a need for a programme like Football Fans and Betting to tackle gambling harm. What does this mean for understanding the role of sports-based interventions for men at risk of gambling harm? Our study showed that promoting interventions to prevent gambling harm within professional football clubs is very difficult, especially when those clubs have partnerships with gambling companies. Future efforts might need to focus on community-based programmes not influenced by commercial gambling ties. Early intervention remains crucial in preventing serious harms from gambling.